Applicability of Fine-Needle Aspiration Biopsy of Lymph Nodes Using WHO Reporting System: Comparison between Pediatric and Adult Brazilian Populations - Ficoto, Leonardo Fávaro; Júnior, Deolino João Camilo; Nora, Gustavo Resende; Valente, Vitor Bonetti [UNESP]; Bernabé, Daniel Galera [UNESP]; Xavier-Júnior, José Cândido Caldeira (Karger Publishers, 2025)
INTRODUCTION: Fine-needle aspiration biopsy (FNAB) is a minimally invasive diagnostic method widely used in the evaluation of lymphadenopathies. However, there are few studies evaluating its applicability in different age groups, especially among the pediatric population. This study aimed to evaluate the cytological findings of lymph nodes FNAB between pediatric and adult patients using the WHO Reporting System for Cytopathology of Lymph Nodes, Spleen. METHODS: This retrospective and observational study included 366 cases of lymph node FNAB collected and analyzed by a single pathological center (the Instituto de Patologia de Araçatuba), Brazil, from January 2016 to December 2024. Cytological diagnoses were categorized using the WHO Reporting System for Cytopathology of Lymph Nodes, Spleen, and Thymus into five categories (inadequate/insufficient, benign, atypical, suspicious for malignancy, and malignant) and correlated with histopathological outcomes, when available. Ancillary techniques and rapid on-site evaluation were not available. Statistical analyses included chi-square and Fisher's exact tests. p < 0.05 was considered statistically significant. RESULTS: Among the 366 cases, 17 (4.6%) were pediatric and 349 (95.4%) were adult. The most frequent location of the lesions was the head and neck region (79%). Benign cytological diagnoses were significantly more common in children (94.1%), while suspicious for malignancy and malignant results were exclusive to adults (29.3% and 14%, respectively; p = 0.001). Larger lymph nodes (>2 cm) were significantly associated with malignancy (p < 0.0001). Considering the total population, the rates of risk of malignancy (ROM) were 50% for category "insufficient," 32.6% for benign, 82.8% for suspicious, and 97.5% for malignant cases. From each category, 28 (53.8%), 49 (27.7%), 35 (71.4%), and 16 (32.6%) patients were underwent histopathological follow-ups, respectively. CONCLUSION: This study, despite the limited pediatric sample, demonstrates that the method is applicable to both pediatric and adult patients, including those outside cancer centers. The calculated ROM was 50% for inadequate, 32.6% for benign, 82.9% for suspicious, and 97.6% for malignant categories. Deviations from WHO reference intervals for inadequate and benign cases may be attributed to the absence of ancillary techniques. Then, two main findings emerged: (i) benign cytological diagnoses predominated in children, while suspicious and malignant results occurred exclusively in adults; and (ii) lymph nodes >2 cm were strongly associated with malignant cytological and histological outcomes.